A Method of Evaluating the Internal Precision of Multi-View Stereo Dense Reconstruction, Applied on Parthenon Frieze - Skarlatos, Dimitrios; Kiparissi, Stavroula; Theodoridou, Sofia; Pandermalis, Dimitrios (My University, 2014)
Recent advances in Structure-fromMotion (SfM) and multi-view stereo (MVS) techniques are getting a lot of attention in the 3D modeling community, as they provide a sophisticated, versatile and rapid way to compute dense 3D point clouds. Many applications in archeology and aerial, surface or underwater surveys have been reported based in the combination of SfM and MVS. In addition, they become more popular and widespread as commercial applications and Internet services are emerging. Nevertheless, there is no known way to evaluate the precision of the extracted point cloud. This paper presents a method for estimating the precision of each point in the final point cloud generated by open source MVS, as it is applied to the Parthenon frieze in the Acropolis Museum.
Keywords: MVS; Precision; Computer vision; Parthenon frieze